Implementation of Ethnomathematical Approach to Datulaya Batik Motifs and Banten Panjunan Motifs in Students' Creative Thinking Ability and Mathematical Resilience - Salmah, Ratu Ummu; Kusuma, Jaka wijaya; Yendra, Novi (Papanda Publisher, 2025)
This research aims to improve the creative thinking ability and resilience of MTs students in mathematics learning through the application of an ethnomathematical approach based on Datulaya and Panjunan batik motifs on geometry transformation materials. The background of this research is based on the low interest of students in mathematics, as well as the weakness of creative thinking skills and students' resilience in facing difficulties, especially in abstract materials such as geometry. The type of research used was quasi-experimental with a pretest-posttest control group design. The experimental class received treatment using an ethnomathematical approach based on local batik motifs, while the control class followed learning with conventional methods. The ability to think creatively mathematically is an important aspect in solving mathematical problems. This study also contains a qualitative descriptive approach to describe creative thinking skills based on the level of resilience of grade IX students of MTs Al-Huda Kelanggaran. The research subjects were classified into three categories of resilience: high, medium, and low. The data collection technique was carried out through questionnaires, tests, interviews, and online documentation. Data is analysed through the process of reduction, presentation, and conclusion. The results of the study show that students with high resilience can provide varied, systematic, and innovative solutions. Students with moderate resilience can present more than one solution, although it is lacking in the aspect of detail. Meanwhile, students with low resilience are only able to give limited answers, even though they are still systematic. This research was carried out quantitatively with a quasi-experimental approach on grade IX students of MTs Al-Huda Kelanggaran, Serang City. The research sample consisted of class IX.1 as an experimental class and IX.3 as a control class, with a total of 30 students. Data analysis used hypothesis tests through the independent sample t-test. The findings of the study showed that the average posttest score of students in the experimental class reached 72.56, while the control class was 64.11. This indicates that the ethnomathematical approach has a more positive influence than conventional methods, especially in improving students' creative thinking skills and mathematical resilience. The use of local batik motifs as a contextual learning medium not only deepens the understanding of mathematical concepts but also fosters a sense of pride in regional culture and shapes the character of students. This study recommends integrating elements of local culture into the mathematics curriculum as an innovative and meaningful learning strategy. To develop students' creative thinking skills optimally, creativity is needed in exploring the mathematical elements contained in the Banten culture. Keywords: Ethnomathematics, Datulaya Batik, Panjunan Batik, Creative Thinking, Mathematical Resilience.